Editorial for JSE 28:3 Fall 2014 - Braude, Stephen (Journal of Scientific Exploration, 2014)
<!–[if gte mso 9]> <![endif]–>The 2014 SSE Conference near San Francisco is now behind us, and I’d rate it as quite successful. Apart from the predictable good times shared with friends whom we see only at these get-togethers, several things in particular stood out for me. First, Gerald Pollack’s Dinsdale lecture on the fourth phase of water was unusually interesting, and in fact all the invited talks were both stimulating and entertainingly presented. (Kudos again to Adam Curry for putting together a really first-rate program, and to Jerry Gin for doing such a wonderful job as local host.) Although I wasn’t monitoring the behavior of attendees generally or invited speakers in particular, I happened to sit near or next to Gerald Pollack for much of the meeting. And I have to say that I was also struck and impressed by his attentiveness and openness to the rest of the program. If he missed a presentation, I didn’t see it, and I believe he took careful notes of most (if not all) of the talks as well. I doubt this was a mere courtesy. I believe Pollack exemplifies the kind of inquisitiveness, open-mindedness, and intellectual courage I at least take to be a prerequisite for membership in the SSE, but which one sees all too infrequently in the Academy, or in the real world generally. Moreover, the conference was quite well-attended, and I was pleased (and somewhat surprised) that many of those present don’t yet qualify for membership in the AARP.1 The shortage of “young blood” has been a concern, not just for the SSE, but also for other similarly minded organizations to which I belong (e.g., the Parapsychological Association and the Society for Psychical Research)2. Indeed, the SSE Council routinely considers ways to encourage the recruitment and participation of new and young members. Brenda Dunne has certainly helped with this by organizing and hosting the New Members and Young Investigators meetings at the annual conferences, and my spies informed me that this year’s meeting was again a success (and not just because the pizza was very good). <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; text-indent:.5in; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Arial","sans-serif"; –> <!–[endif] –>